First evidence of prothymosin alpha localization in the acrosome of mammalian male gametes. Issue 8 (18th April 2013) - Ferrara, Diana; Pariante, Paolo; Di Matteo, Loredana; Serino, Ismene; Oko, Richard; Minucci, Sergio
Abstract Prothymosin α (PTMA) is a highly acidic intrinsically unstructured protein. Its expression in male gonads is evolutionary conserved; in rat testis it is specifically localized in the cytoplasm of post‐meiotic germ cells, in association with the developing acrosome system. In the present paper we investigated on PTMA localization inside the head of mammalian spermatozoa (SPZ). We chose a confocal approach to ascertain whether PTMA is expressed in the acrosome or in the perinuclear theca, two regions that are tightly linked and partially overlapped in the mature haploid cells. The obtained results showed that PTMA is specifically localized in the acrosome of rat epididymal SPZ; the same experimental approach evidenced, for the first time, PTMA presence in human ejaculated SPZ. A Western blot analysis on protein extracts from human sperm head fractions confirmed the confocal data and demonstrated that the peptide is specifically associated with the inner acrosomal membrane fraction. Finally, when the acrosome reaction was induced in vitro by progesterone treatment on both rat and human sperm, PTMA signal was retained in the apical region of reacted SPZ. In conclusion, this study confirms the conservation of PTMA distribution in vertebrate male gametes and strongly supports a role for this polypeptide in their physiology. J. Cell. Physiol. 228: 1629–1637, 2013. © 2013 Wiley Periodicals, Inc.